TASYBIH AT-TAMTSIL DALAM AL-QURÎ„AN: ANALISIS BALAGHAH PADA SURAH AL-KAHFI - Ferki Ahmad Marlion; Kamaluddin Kamaluddin; Putri Rezeki (IAIN Batusangkar, Indonesia, 2021)
This article aims to analyze the verses of Tasybihat-tamtsil in Qurâ€™an surah al-Kahf. The research used Balaghah analysis approach and literature review method. Tasybih is usually used to convey very important and crucial issues, such as issues of aqeedah, a description of people who believe in Allah, issues around shirk and the condition of the polytheists, as well as various other great practices. The result of the research explained that there are two Tasybihat-tamtsil in surah al-Kahf, first, the parable of a man who prided himself on fruitful garden and rivers flowing. He thought that he will not perish forever and deny the Day of Judgment. Then, when all perish, he could only regret his wrong assumption while living in this world. Second, the parable of life that vanished in the blink of an eye. This is a rational Tasybihat-tamtsil that describes something that can no longer be returned. Allah SWT ensure that the beautiful world will dissapear.Â